The Spanish Civil War and the Construction of a Reactionary Historical Consciousness in Augusto Pinochet's Chile. - Weld, Kirsten (Hispanic American Historical Review, 2018)
In 1976, Augusto Pinochet told Henry Kissinger that Chile was undergoing "a further stage of the same conflict which erupted into the Spanish Civil War." Pinochet was not alone in this view; throughout the 1970s, Chilean rightists used the Spanish Civil War as a point of reference. This article explores how and why Chilean golpistas drew on the Spanish example in developing their ideas about political struggle. It argues that the Civil War--or at least one interpretation of it, in which the military had purged Spain of communism in a kind of Christian reconquest--was a key component of the paradigm that some anti-Salvador Allende revanchists used to understand their world. In so doing, the article sheds light on a strain of Chilean conservatism that looked not to the United States for inspiration but to Spain, demonstrating the value of integrating Europe into analyses of Cold War Latin America's transnational dimensions.